Grain setting defect1 (GSD1) function in rice depends on S-acylation and interacts with actin 1 (OsACT1) at its C-terminal - Gui, Jinshan; Zheng, Shuai; Shen, Junhui; Li, Laigeng (Frontiers in Plant Science, 2015)
Grain setting defect1 (GSD1), a plant-specific remorin protein specifically localized at the plasma membrane and plasmodesmata of phloem companion cells, affects grain setting in rice through regulating the transport of photoassimilates. Here, we show new evidence demonstrating that GSD1 is localized at the cytoplasmic face of the plasma membrane and a stretch of 45 amino acid residues at its C-terminal is required for its localization. Association with the plasma membrane is mediated by S-acylation of cysteine residues Cys-524 and Cys-527, in a sequence of 45 amino acid residues essential for GSD1 function in rice. Furthermore, the coiled-coil domain in GSD1 is necessary for sufficient interaction with OsACT1. Together, these results reveal that GSD1 attaches to the plasma membrane through S-acylation and interacts with OsACT1 through its coiled-coil domain structure to regulate plasmodesmata conductance for photoassimilate transport in rice.